Terra, poder e violência: conflitos no Mato Grosso do Sul e a relação do agronegócio com os Kaiowá e Guarani - Daniel Macedo Lopes Vasques Monteiro (Confins)
Mato Grosso do Sul according to the Atlas of Brazilian Agriculture (2017) has 92% of its territory occupied by private lands. Of this part 83% are from large estates. Indigenous Lands represent only 2% of the total state. The land-use scenario in Mato Grosso do Sul shows the inequality that exists in rural areas, resulting in the expulsion of indigenous people from their original lands, as a consequence of the historical process of violence perpetuated by agribusiness actions and practices in the current period. The aim of this study is to understand the conflict in the disputed territory and the violent actions of capital, mainly agribusiness, against the Kaiowá and Guarani people. It is fundamental to understand the concepts of power and violence (Arendt, 1985), and thus understand how agribusiness acts when trying to impose itself on these indigenous people. It is worth noting that in addition to the bibliographic review, research was done on news and social movements sites that contribute to the debate about the violence that occurs in the land dispute. Field work was carried out.